Environmental Sanitation Awareness Attitude Towards Personal Health Behavior of Junior High School Students in Ternate - Yusuf, Yusmar; Bahtiar, Bahtiar; Tala, W.D. Syarni (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
Awareness of environmental sanitation among adolescents not only contributes to pro-environmental behavior, but it may also be related to personal health behavior. This study aims to analyze the relationship and influence of environmental sanitation awareness attitudes on the personal health behavior of junior high school students in Ternate City, North Maluku Province. The study uses a quantitative approach with a correlational (cross-sectional) design involving 122 junior high school students. Data were collected through questionnaires on environmental sanitation awareness attitudes and personal health behavior within a score range of 0–100. Data analysis included descriptive statistics, prerequisite tests (residual normality, linearity, and homoscedasticity), Pearson correlation, and simple linear regression. Descriptive results showed an average environmental sanitation awareness attitude score of 83.47 (SD=6.87) and an average personal health behavior score of 72.28 (SD=6.85). Pearson correlation test showed a strong positive relationship between environmental sanitation awareness and personal health behavior (r=0.714; p<0.001). Simple linear regression indicated a significant effect with R²=0.510 and the model equation Y = 31.725 + 0.716X, meaning that a one-unit increase in environmental awareness predicts a 0.716-point increase in personal health behavior. These findings underscore the importance of integrating environmental education in schools as a dual strategy to enhance ecological concern while supporting healthy lifestyle behaviors among adolescents.